Extraction of wood vinegar from bagasse and its application as bio-reducer to produce stable silver nanoparticles with enhanced antibacterial activity - M. Ahasanur Rabbi; Rasheda Akter; Most. Halima Khatun; Firoz Ahmed; Hurey Jahan Kadri; Bijoy Maitra; M. Zia Uddin Rasel; Md. Al-Amin; Syed Rashel Kabir; M. Rowshanul Habib (Heliyon)
Global efforts have been made to address environmental and health concerns by promoting and adopting renewable natural resources. This study investigated the role of bagasse-based wood vinegar to synthesize and stabilize silver nanoparticles. We present a simple bottom-up approach to produce silver nanoparticles using the green reducing agent. Wood vinegar has been used to create and stabilize nanoparticles as well as increase the biological activity of silver nanoparticles. In the WV-AgNPs aqueous dispersion's absorption spectra, a wide surface plasmon resonance (SPR) peak with a 395 nm wavelength center was visible. Wood vinegar has been utilized not only to synthesize and stabilize nanoparticles, but it also makes silver nanoparticles biologically more active. Prepared WV-AgNPs showed remarkable antibacterial activity against three pathogenic bacteria and satisfactory antiproliferative activity against human breast (MCF-7) cell line. The stability of the prepared nanoparticles has been confirmed by zeta potential value. The surface morphology and the particle size were investigated by scanning electron microscope and transmission electron microscope. The prepared particles are spherical in shape and particle size ranges from 20 to 40 nm. WV-AgNPs are further characterized by UV–Vis spectroscopy, X-ray diffraction (XRD), Thermogravimetric analysis (TGA), Dynamic Light Scattering (DLS), Energy-dispersive X-ray spectroscopy (EDX) and Fourier transform infrared (FTIR) spectroscopy. Based on the results, it can be concluded that silver nanoparticles mediated by wood vinegar showed promising properties and might find application in the biological domain.